PERTUMBUHAN Grynops vesteegi (Giil) PADA BERBAGAI DOSIS PUPUK ORGANIK CAIR G-TONIK - Timur Kogoya; Marthen T. Lasut; Johan A. Rombang (COCOS, 2016)
ABSTRACTThe study of the growth of Gyrinops vesteegii (Giil) plant by applying various doses of G-tonic liguid organic fertilizer had been carried out in the Greenhouse of the Faculty of Agriculture, University of Sam Ratulangi Manado.The purpose of this study is to find out the effect of various doses of liguid organic fertilizer on the growth of the Gyrinops vesteegii plant. This study is conducted by using Randomized Complete Block Design ( RCBD) with 5 treatments and 5. Replications each replication consists of one plant. The treatments applied were P1 (Control, without fertilizer), P2 0.125 cc of G – tonic liguid organic fertilizer given every application. P3 0,25 cc, P4 0,375 cc, and P5 0,500 cc. The variables observed were the increase of plant,s height as well as of stalk diameter. The data obtained will be analyzed by using Analisisv of Variance (anova) at 5% level.The result of the study showed that the application of G-tonic liguid organic fertilizer to Gyrinops vesteeglii plant seedling did not have significant effect on the increase of plant,s height and stalk,s diameter. This is due to the liguid organic fertilizer did not have yet effect toward the Gyrinops vesteeglii plant seedling in a period of 35